EFFICAIENCY OF BLACK ANT WORKERS Messor rufitarsis (Fab.) WORKERS IN DISPERSING UN CULTIVATED SEEDS - Nada S. Othman (Mesopotamia Journal of Agriculture)
The efficiency of ant workers Messor rufitarsis in transmitting of un culturing seeds during the years of 2004 and 2005 were studied, It was found that ant workers dispersed the seeds of lettuce, cabbage, snake cucumber, barley, muskmelon and wheat untreated with cruiser insecticide in addition to the seeds of the last two types of seeds treated with insecticide that placed at the dimensions of 0.1, 2, 4, 6, 8 & 10 m. Far from the ant nest opening, while the seeds of parsley, cress and celery that treated with the insecticide and placed at 10 m. Far from the nest opening with were remained with value of average 23.66, 23.46 & 22.26 seeds, respectively In 2005, M. rufitarsis the ant workers had dispersed all the treated and untreated seeds with insecticide which comprised snake cucumber, grass, wheat, barley, radish and cauliflower in addition to the untreated seeds with the insecticide for each of muskmelon, parsley, carrots, table beet, squash and cabbage that is placed at 0.1 m. Far from the nest opening.